2019
DOI: 10.1053/j.ajkd.2019.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Decision Aid for Patients Considering Peritoneal Dialysis and In-Center Hemodialysis: A Randomized Controlled Trial

Abstract: US patients face the difficult choice between the most common dialysis types, in-center hemodialysis and peritoneal dialysis. This study evaluated the value of a new decision aid to assist in the choice of dialysis modality. Study Design: A parallel-group randomized controlled trial to test the efficacy of the decision aid on decision-making outcomes. Setting & Participants: English-speaking US adults with advanced chronic kidney disease and internet access enrolled in 2015. Intervention: Participants randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 44 publications
1
25
0
2
Order By: Relevance
“…41 Patient decision aids can also better prepare patients to select a treatment option that they believe is best for them. 42 Additionally, engaging specialty palliative care and ethics consultation services in the care of complex patients can be helpful to patients, families and clinicians and reduce the use of burdensome or unnecessary treatments. 43,44 Taken together, our findings call for more innovation to support shared decisionmaking for treatment of advanced CKD.…”
Section: Discussionmentioning
confidence: 99%
“…41 Patient decision aids can also better prepare patients to select a treatment option that they believe is best for them. 42 Additionally, engaging specialty palliative care and ethics consultation services in the care of complex patients can be helpful to patients, families and clinicians and reduce the use of burdensome or unnecessary treatments. 43,44 Taken together, our findings call for more innovation to support shared decisionmaking for treatment of advanced CKD.…”
Section: Discussionmentioning
confidence: 99%
“…However, the review includes no decision aids specifically for nephrological care. A randomized study among 133 CKD patients concludes that an online decision aid can improve knowledge and decrease decisional conflict and uncertainty about choice of dialysis treatment [ 54 ]. So, decision aids are important for use during dialysis education.…”
Section: Discussionmentioning
confidence: 99%
“…DOI: 10.1159/000509711 Shared decision-making for ESRD treatments should encompass conversations between clinicians, patients, and caregivers about the risk and benefits of both dialytic and non-dialytic treatments in the context of a patient's goals and values [39]. However, despite long-standing advocacy for supportive kidney care delivery among national and international nephrology organizations, educational tools that inform patients and their loved ones are limited and fewer have established efficacy on objective knowledge [14,17,19,40,41]. We demonstrated that a supportive kidney video decision aid was well received among our study cohort-which counters historic beliefs among clinicians that speaking about non-dialytic treatments may cause unintended psychological harm toward patients [42].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with advanced CKD and their caregivers desire patient-centered information regarding their ESRD treatment options but supportive kidney care is often not discussed [11][12][13]. Also, there is limited evidence about how best to inform patients about non-dialytic treatments and pre-dialysis education program processes vary widely [14][15][16][17][18][19]. Educational video decision aids have been studied in randomized controlled trials (RCT) to better promote informed decision-making among patients with kidney disease, dementia, heart failure, and cancer; however, none have included supportive kidney care [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%